2019
DOI: 10.1007/978-3-030-23281-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Discourse-Driven Argument Mining in Scientific Abstracts

Abstract: Argument mining consists in the automatic identification of argumentative structures in texts. In this work we address the open question of whether discourse-level annotations can contribute to facilitate the identification of argumentative components and relations in scientific literature. We conduct a pilot study by enriching a corpus of computational linguistics abstracts that contains discourse annotations with a new argumentative annotation level. The results obtained from preliminary experiments confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Regarding argument relations, there have been also attempts to distinguish them into supporting and attacking. However, Accuosto and Saggion (2019) did not found any attack relation in 60 abstracts of the SciDTB corpus (Yang and Li, 2018). Also, Lauscher et al (2018) and Mayer et al (2020) found that the number of attacking relations in full papers and abstracts is relatively low.…”
Section: Annotation Schemamentioning
confidence: 90%
See 3 more Smart Citations
“…Regarding argument relations, there have been also attempts to distinguish them into supporting and attacking. However, Accuosto and Saggion (2019) did not found any attack relation in 60 abstracts of the SciDTB corpus (Yang and Li, 2018). Also, Lauscher et al (2018) and Mayer et al (2020) found that the number of attacking relations in full papers and abstracts is relatively low.…”
Section: Annotation Schemamentioning
confidence: 90%
“…The most common argumentative relationships employed are the "support" and "attack" ones (Peldszus and Stede, 2013;Mayer et al, 2020). Researchers also adapt additional relation types from Rhetorical Structure Theory (Mann and Thompson, 1988) such as "semantically same" (Lauscher et al, 2018), "detail", "sequence" (Kirschner et al, 2015), and "additional" (Accuosto and Saggion, 2019). Although those fine-grained relation types are of great value, their presence in the context of a scientific abstract is limited.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of such a corpus, the task is to establish the relationship between rhetorical and argumentative structure of the text, the correlation of the components and relations between them in order to use existing resources and tools of discourse analysis to extract arguments. So, [9] describe the development and use in experiments of a two-level corpus of 112 short texts written in the genre of argumentative essays, and in [1], the material for annotation are scientific articles from the field of computer linguistics.…”
Section: Introductionmentioning
confidence: 99%